Female characters in the skeptical fiction of Machado de Assis - Soares, Daniel Benevides (Argumentos - Revista de Filosofia, 2020)
This paper aims to present the role of female characters in the skeptical fiction of Machado de Assis. We take as a basis the interpretation of José Raimundo Maia Neto. According to the author, this skeptical fiction presents the development of a narrator throughout Machado’s fiction. The article is divided into three parts. In the first, the type of skepticism present in Machado’s work according to Maia Neto is presented in its most important elements. In the second, the comprehensive meanings of female characters in this context are discussed in general. In the third, some of the Machado’s characters are analyzed individually.